2015
DOI: 10.1080/08927022.2015.1059938
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the molecular mechanism of methanol-induced inactivation ofThermomyces lanuginosuslipase: a molecular dynamics simulation study

Abstract: Methanol intolerance of lipase is a major limitation in lipase-catalyzed methanolysis reactions.In this study, to understand the molecular mechanism of methanol-induced inactivation of lipases, we performed molecular dynamics (MD) simulations of Thermomyces lanuginosus lipase (TLL) in water and methanol and compared the observed structural and dynamic properties. The solvent accessibility analysis showed that in methanol, polar residues tended to be buried away from the solvent while non-polar residues tended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…It is important to note that the structural changes detected in the water-ethanol mixtures do not necessarily represent a transition toward a catalytically competent lipase. Indeed, as indicated by molecular dynamics simulations of TLL, methanol does not accommodate structural changes allowing formation of the oxyanion hole [114,115]. Hence, the changes in bimane-Trp interaction detected by TrIQ are ascribed to structural movements associated with lid-opening, but not to an active conformation.…”
Section: Detecting Structural Movements Associated With Lipase Activamentioning
confidence: 99%
“…It is important to note that the structural changes detected in the water-ethanol mixtures do not necessarily represent a transition toward a catalytically competent lipase. Indeed, as indicated by molecular dynamics simulations of TLL, methanol does not accommodate structural changes allowing formation of the oxyanion hole [114,115]. Hence, the changes in bimane-Trp interaction detected by TrIQ are ascribed to structural movements associated with lid-opening, but not to an active conformation.…”
Section: Detecting Structural Movements Associated With Lipase Activamentioning
confidence: 99%
“…Such an “activation” of the enzyme is naturally favored in a solvent possessing either a hydrophobic character or a low dielectric constant. The separation and purification of the product become easier as well during such interfacially immobilized enzymatic catalysis (immobilized on the large hydrophobic surface of an aggregated substrate or surfactant) than that when the reaction is carried out with chemical catalysts. , Among all lipases, those from the thermophilic fungus Thermomyces lanuginosus (TL) are found to be industrially significant for biodiesel production, owing to their inherent stability at a high temperature, operation over a wide range of pH conditions, as well as their high methanolysis activity. TL lipase (TLL) has been used not only in biodiesel production but also in the food industry, in the enantiomeric separation of racemic mixtures and in many regioselective or regiospecific processes to synthesize fine chemicals . Rightfully, TLL has been studied by several researchers through in vitro experiments, site-directed mutagenesis, X-ray crystal structures, , site-directed spin labeling, intrinsic tryptophan fluorescence studies, , and molecular dynamics simulations. ,, …”
Section: Introductionmentioning
confidence: 99%
“…However, several reports in the literature have also suggested that alcohol causes inactivation and/or thermal destabilization of the enzyme. A very recent simulation study of TLL in methanol has explored the details of the molecular mechanism behind this inactivation …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations